2013
DOI: 10.6065/apem.2013.18.4.191
|View full text |Cite
|
Sign up to set email alerts
|

The difference in serum alkaline phosphatase levels between girls with precocious puberty and those with normal puberty

Abstract: PurposeSerum alkaline phosphatase (ALP) level is the most valid marker of bone formation. Precocious puberty (PP) in girls is characterized by early growth acceleration. The aim of this study was to determine whether serum ALP levels differ between girls with PP and those with normal puberty, and whether ALP level varies with age or Tanner stage.MethodsThis retrospective study included girls with PP (n=61) and normal puberty (n=71) who visited the outpatient clinic at Department of Pediatrics, Chungnam Nationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The results revealed that, compared with the other groups, treatment with APE in the long term slightly reduced the body length of rats ( Figure 3 b). We also measured the serum ALP level, a marker of bone maturation [ 19 ], to evaluate the effect of APE on regulating the growth rate. Only leuplin showed an inhibitory effect to restore the serum ALP concentration to the basal level; however, APE treatment did not change the serum ALP level in the PP model ( Figure 3 c).…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that, compared with the other groups, treatment with APE in the long term slightly reduced the body length of rats ( Figure 3 b). We also measured the serum ALP level, a marker of bone maturation [ 19 ], to evaluate the effect of APE on regulating the growth rate. Only leuplin showed an inhibitory effect to restore the serum ALP concentration to the basal level; however, APE treatment did not change the serum ALP level in the PP model ( Figure 3 c).…”
Section: Resultsmentioning
confidence: 99%
“…As plasma ALP levels are closely related to osteoblastic activity and bone growth, ALP activity is generally higher in younger individuals 27 . Findings in the current study align with this phenomena, as predose KK/HlJ mice (6 weeks of age at necropsy) had numerically higher plasma ALP activity compared with that of the postdose, vehicle-treated C57BL/6J mice and postdose, vehicle-treated control KK/HlJ mice (both 20 weeks of age at necropsy; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…From some salivary components, there are few components that sounds interesting to be observed in accordance to dental aging and maturation. One of them is alkaline phosphatase, in which the application for bone growth isn’t no longer debatable 30 .…”
Section: Introductionmentioning
confidence: 99%